1997
DOI: 10.1021/bi9700476
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Evidence for Folding and Unfolding Intermediates in Staphylococcal Nuclease

Abstract: The complex kinetic behavior commonly observed in protein folding studies suggests that a heterogeneous population of molecules exists in solution and that a number of discrete steps are involved in the conversion of unfolded molecules to the fully native form. A central issue in protein folding is whether any of these kinetic events represent conformational steps important for efficient folding rather than side reactions caused by slow steps such as proline isomerization or misfolding of the polypeptide chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
156
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(179 citation statements)
references
References 67 publications
23
156
0
Order By: Relevance
“…The lag phase rate increases from 45 s Ϫ1 at pH 5.3 to 200 s Ϫ1 at pH 8.5. These results agree closely with published data as noted in Table 1 (12,26,27).…”
supporting
confidence: 93%
See 1 more Smart Citation
“…The lag phase rate increases from 45 s Ϫ1 at pH 5.3 to 200 s Ϫ1 at pH 8.5. These results agree closely with published data as noted in Table 1 (12,26,27).…”
supporting
confidence: 93%
“…The plot of residuals shows the reality of the lag phase, which is confirmed by similar results at other conditions and in other laboratories (see Table 1). (27). ‡ Unfold at pH 2.0, measure folding at pH 6.0, 20°C, 0.1 M sodium cacodylate, 2 mM EGTA (12).…”
mentioning
confidence: 99%
“…Unambiguous identification of a folding pathway is possible only by direct examination of the intermediates formed during unfolding or folding processes, either using time-resolved techniques (60) or perhaps from dynamic simulations. For SNase, recent examination of a folding and unfolding mechanism by stopped-flow fluorescence techniques revealed the occurrence of a partially folded state with a stable -domain and a largely disordered R-helical region (61). Interestingly, the three highest peaks obtained here coincide with the strands 2, 3, and 5, which could lend support to a relationship between early formation and high stability.…”
Section: Results and Comparison With Hx Experimentssupporting
confidence: 60%
“…These isolated stable subdomains clearly re£ect the modular nature of SNase. In a previous kinetic folding study of SNase, the location of the usual structure reporters in SNase, such as the Khelices or the single tryptophan at the position 140 being outside the L-subdomain prevents direct characterization of the kinetic phase involving the rapid formation of L-barrel [11]. The V66W110 and G88W110 with a single £uorescence reporter in the L-barrel are expected to be suitable for kinetic folding studies of the isolated L-subdomain.…”
Section: Discussionmentioning
confidence: 99%
“…Pulsed hydrogen exchange and NMR methods showed an early protection of hydrogen in part of the L-barrel indicating that the L-barrel is the ¢rst formed structure unit in SNase [10]. Kinetic folding and unfolding studies of a proline-free SNase also revealed a folding intermediate which is consistent with a partially folded state having a stable L-barrel and a largely disordered K-helical region [11]. These suggest that the structure of SNase can be split into two subdomains, with predominantly K-helix and L-sheet, respectively.…”
Section: Introductionmentioning
confidence: 99%